(untitled) (Journal of Global Accounting, 2024)
This study examined the effect of the National Housing Fund on the Nigerian economic growth from 1995to 2022. The study employed the ex post facto research design using Primary Mortgage institutions as the population of study. Sampling was considered unnecessary as aggregate statistical data were used. The National Housing Fund Scheme was assigned proxy of Loans and investments of Primary Mortgage Institutions. The Nigerian economic growth was measured using Gross Domestic Product (GDP). Data for the study were extracted from the 2019 CBN HDI. Specifically, the study found that the National Housing Fund Scheme significantly and positively affect Gross Domestic Product (GDP) of Nigeria. The study concludes therefore, that the NHF is a significant stimulator of the Nigerian economy in terms of productivity. The study recommended increased supervisory and funding support for the NHF scheme to ensure the goals are achieved.